Cross-ownership and Corporate Innovation - Zhang, Wenlu (Transactions on Economics, Business and Management Research, 2024)
This article takes Chinese A-share listed companies from 2014 to 2022 as the research sample, and uses a multiple regression model to empirically test the relationship between cross-ownership and corporate innovation efficiency. Research has found that: (1) cross-ownership can improve the innovation efficiency of enterprises. (2) when the internal control quality of the enterprise is high and the legal system environment is good, the promoting effect of Cross-ownership on the innovation efficiency of the enterprise is more significant.